Assessment of diversity in anti-nutrient profile, resistant starch, minerals and carbohydrate components in different ricebean (Vigna umbellata) accessions. (30th March 2023) - Sharma, Paras; Goudar, Giridhar; Kumar Chandragiri, Anil; Ananthan, R.; Subhash, K.; Chauhan, Anitha; Longvah, T.; Singh, Mohar; Bhardwaj, Rakesh; Parida, Swarup Kumar; Singh, Amit Kumar; Gayacharan,; et al.
Highlights: Ricebean accessions (n = 38) were analyzed for nutrients and anti-nutrient profile. None of the sample exhibited phytic acid:Fe molar ratio below the critical value. Among ricebean accessions, n = 21 (56 %) had higher protein content (>25.36 g/100 g). Nine ricebean accessions showed high nutrients and low anti-nutrients content. The higher SDF and RS were observed in 16 and 23 samples. Abstract: Ricebean accessions (n = 38) cultivated in India were evaluated for their comprehensive nutrient, anti-nutrients and mineral composition. Protein and total dietary fibre ranged between 23.23 and 27.33 and 12.27 to 16.69 g/100 g, respectively. Among the oligosaccharides, verbascose was not detected, however, raffinose and stachyose ranged between 47 and 186 and 117 to 5765 mg/100 g, respectively. Among the free sugars, sucrose was found dominating (up to 370 mg/100 g). Resistant starch (4.13 to 8.62 %), iron (3.49 to 7.46 mg/100 g), zinc (1.90 to 3.72 mg/100 g) and selenium (0.28 to 4.48 µg/100 g) varied significantly (p < 0.05) among ricebean samples. Phytic acid, saponin, trypsin inhibitor and oxalate analysed in ricebean accessions ranged between 303 and 760 mg/100 g, 19 to 46 mg/g, 309 to 1076 mg/100 g and 219 to 431 mg/100 g, respectively. Multivariate analysis using hierarchical clustering analysis (HCA), and principal component analysis (PCA) was employed to decipher the diversity of nutrients and anti-nutrients across the ricebean accessions. Based on HCA, dendrogram-1 (nutrients) and dendrogram-2 (minerals, anti-nutrients) were produced, having four clusters in each. In the dendrogram-1 and 2, the largest cluster had (n = 21) and (n = 15) accessions, respectively. The PCA analyse the uncorrelated set of variables (principal components) and it condenses a large set of data variables. Based on the eigenvalue >1, a total of eight PCs were formed contributing total variance of 78.8 %. The factor loading contribution in the PC1 and PC2 were from iron, fructose, glucose, raffinose and total dietary fibre, selenium (Se) and protein, respectively.